(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
As part of its EU accession agenda, Republic of North Macedonia has performed series of reforms of its legal system in order to reach EU legal standards. As part of this agenda, improvement of the efficiency of the criminal trials was marked as highly relevant. New Law on Criminal Procedure, consisting many modern adversarial trial instruments, enacted in 2010, supposed to improve the efficiency of the Macedonian criminal trials. However, after a certain period we deem that it is necessary to reevaluate the effects of these reforms and their practical implementation. Hence, the author evaluates the Macedonian court’s practice of implementation of the defendant’s guilty plea during the main hearing of the criminal procedure together with the reasons for decline in the use of these instruments into the court’s practice. The main reasons for such decline of the implementation in practice can be located in several areas. Such areas are improper implementation of the law, legal imperfections together with the length of the criminal trials, lesser sanctioning policy and absence of proper instrument for providing of the expected sentence as an outcome from the bargaining procedure. However, besides these already known weak areas concerning the implementation of these instruments in practice the author has detected an additional problematic area about the factual support of the guilty plea during the main hearing. In addition, the author analyzes the practice of evaluation of additional evidence in case of guilty plea, and the amount and the quality of evidence provided by the prosecutor as support to the defendant’s guilty plea. Author concludes that there is a gap between the theoretical definitions of the guilty plea and its practical implementation, and provides practical proposals for improvement of the provisions of the Law on Criminal Procedure. He concludes that these amendments are necessary for proper implementation of the Law and of the protection of the defendant’s rights and pertaining the impression of just criminal procedure in cases when defendant pleads guilty.